Effects of Dietary Protein and Fish Density on Performance and Production Economics of Golden Shiners in Pools. (21st March 2014) - Lochmann, R. T.; Phillips, H.; Weldon, D.; Stone, N.; Engle, C.
Abstract: We conducted an outdoor feeding trial with Golden Shiners Notemigonus crysoleucas using diets with 22% or 28% protein from different sources. The 28% protein diet with soybean (SOY) meal was the control, and the three other diets contained 22% protein mainly from SOY, corn gluten feed (CGF), or corn distillers dried grains with solubles (DDGS). The 22% protein SOY diet was also offered as a meal or pellet in separate treatments. Each of the five diets was fed to fish at two densities: 250, 000 fish/ha (low density) or 750, 000 fish/ha (high density). Fish with an initial weight of 0.25 ± 0.003 g (mean ± SE) were stocked into four 4.1‐m 3 pools per treatment and fed daily to apparent satiation for 9 weeks. Diet effects were assessed by measuring growth, survival, feed conversion, condition index, and body composition. An enterprise budget analysis was conducted to determine the economic effects of different treatments. Fish weight gain was higher at the low density regardless of diet. Weight gain was also higher in fish fed the diet with 28% protein than in those fed other diets at either density. Relative weight ( Wr ) was higher at the high density and in fish fed the SOY diets compared with those fed the CGF or DDGS diets. Survival was higher at the high density, and no diet effects were apparent. Gross yield was higher at the high density and in the 28% protein SOY control. Feed conversion ratio was better at the low density. Whole‐body lipid was higher in fish at the low density. The most economically beneficial diet was the 28% protein SOY diet, but producers must consider feed choice in the context of their overall business model. The 22% protein diets were inadequate for rapid growth, but did not compromise survival, indicating a possible use for maintenance feeding when fish reach market size.